KELAYAKAN TARUSAN KAMANG SEBAGAI DESA WISATA DI KABUPATEN AGAM (ANALISA ASPEK PASAR DAN PEMASARAN) - SE. MM, Dewi Anggraini. (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Tarusan Kamang as one of the newly developed tourist villages is an example of theempowerment of local communities to introduce west sumatera culture to tourists and toimprove their standard of living as a by-product. The purpose of this study is to analyse thefeasibility of developing a Tourism tarusan kamng by analysing aspects of markets andmarketing, legal, technical and operational, human resources, economic and financial.Through analysis of the three competitors it can be seen that tasusan kamng has anindependent website . Marketing strategies undertaken include: determination of the locationstrategy, pricing Strategy with the method of cost plus pricing, and product growth strategiesin which the services of a quality product better or different from other tourist , promotionthrough the website, the offensive strategy is a strategy which is focused on change efforts toachieve a better level and training of human resources.Key words: tourism potential, strategies, feasibility analysis